A comparison of the effects of local and EAT-Lancet dietary recommendations on selected economic and environmental outcomes in India - Singh, Vartika; Stevanović, Miodrag; Bodirsky, Benjamin Leon; Mishra, Abhijeet; Ghosh, Ranjan Kumar; Popp, Alexander; Lotze-Campen, Hermann (Elsevier, 2025)
The global discourse is nearly unanimous that dietary transitions are crucial to achieve sustainability goals. In this context, healthy dietary recommendations offer demand-side solutions towards minimizing environmental impacts from food production. However, these guidelines have also faced some criticism for their blanket approach and limited consideration of regional preferences. Using a validated food-economy-environment integrated modelling framework, we compare between two types of healthy diets − the globally recommended EAT-Lancet diets and Indian government’s National Institute of Nutrition (NIN) local diets − by examining their impacts on agricultural production, agricultural commodity prices, food expenditures, trade impacts, Greenhouse gas (GHG) emissions and water withdrawals. Our results suggest that the adoption of regional recommendations (NIN diets) lead to better outcomes for select economic and environmental indicators. When India shifts to NIN diet, its domestic demand for cereal crops decreases, leading to a 36 % reduction in cereal crop production by 2050 and change in demand for sugars and animal-sourced foods (ASFs). This has the potential to reduce commodity prices of food by upto 24 % by 2050. A shift to the NIN diet in India reduces methane (CH4) emissions by 36 % and N2O by 35 % compared to business-as-usual, performing better than the EAT-Lancet diet, which reduces CH4 emissions by 13 %. Water withdrawals reduce almost by the same value under both the dietary scenarios primarily due to lesser dependence on cereal crops and livestock products. These findings remain consistent in our sensitivity analysis, with varying global trade scenarios, offering greater benefits of food systems transformation through liberal trade policies. Our analysis underscores the pivotal role of regional inclusivity in global assessments, enhancing our comprehension of how food systems can be reimagined to align with both food security and environmental sustainability.